Risk in child protection assessment challenges and frameworks for practice - Calder, Martin C.; Archer, Julie (London Jessica Kingsley Publishers, 2016)
In this accessible guide to assessing risk in child protection, Martin C. Calder outlines the relevant policy, introduces debates about what risk means, identifies the key challenges for practice, summarizes the evidence base for effective assessment and provides a helpful framework for front line workers.
Keywords: Child welfare -- Great Britain; Child abuse -- Prevention; Child sexual abuse -- Prevention; Risk management